Parallel grafting technique for a complex zone 6 aortic pseudoaneurysm treatment - Azevedo Mendes, Daniel (2023)
INTRODUCTION: Endovascular reconstruction of the thoracoabdominal aorta is highly complex due to the need to preserve the main visceral branches. Optimal treatment with fenestrated and branched aneurysm aortic repair (F/B-EVAR) is usually not possible in urgent situations. Parallel grafting technique as an “off-the-shelf” solution have been described with good short and medium-term results. CASE REPORT: A 44-year-old male, born in Guinea Bissau, presents to the emergency department with epigastric pain radiating to the dorsum. The patient had a history of large vessel vasculitis secondary to Bechet’s disease (HLA B51 allele positivity) and previous thoracic aneurysm aortic repair (TEVAR) to treat a paraceliac aortic pseudoaneurysm. Computed tomography angiography (CTA) demonstrated a pseudoaneurysm with approximately 10 cm diameter at zone 6 immediately distal to the previous endoprosthesis. The pseudoaneurysm was excluded with a parallel grafting technique using a 31mm aortic endoprosthesis with a periscope graft for the right renal artery in a “sandwich-like” configuration and a chimney graft for the superior mesenteric artery (SMA). Postoperative CTA confirmed the exclusion of the pseudoaneurysm and permeable bridging stents. CONCLUSION: The pathology of the thoracoabdominal aorta is technically demanding, requiring experience and detailed planning. The complexity increases in emergency cases. Our case highlights that the parallel grafting technique should be encouraged in life-threatening scenarios as a readily available solution for complex aortic repair, even in a reconstructed aorta.